Regenerating Urban Land : A Practitioner's Guide to Leveraging Private Investment - Amirtahmasebi, Rana; Orloff, Mariana; Wahba, Sameh; Altman, Andrew (World Bank, Washington, DC, 2016)
Regenerating Urban Land draws on the experience of eight case studies from around the world. The case studies outline various policy and financial instruments to attract private sector investment in urban regeneration of underutilized and unutilized areas and the requisite infrastructure improvements. In particular, each case study details the project cycle, from the scoping phase and determination of the initial amount of public sector investment, to implementation and subsequent leveraged private-sector funds. This manual analyzes rates of return on the investments and long-term financial sustainability.